2021
DOI: 10.7759/cureus.16598
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of ABO Blood Group to the Severity of Coronavirus Disease: A Cross-Sectional Study From a Tertiary Care Hospital in Karachi

Abstract: BackgroundBlood groups are considered to have an impact on the occurrence and severity of coronavirus disease. While among Chinese and Caucasian, blood group O individuals were less and group A were more likely to have severe disease and mortality, data on South Asians aren't available. ObjectiveThis study aimed to find out the association of disease severity with blood group among coronavirus disease 2019 (COVID-19) patients. Materials and methodologyData were collected on a predesigned questionnaire containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
2
1
2
Order By: Relevance
“…In his detailed analysis, Bhattacharjee further supported this with data indicating a higher frequency of Blood Group-A in patients with severe COVID-19. 24 Our study diverges from the results obtained by Rehman FU et al, 25 Hafiz W et al 26 and Bryce E Pasko et al 27 who found no significant association between blood groups and disease severity. In studies by Barnkob et al 28 and Dite et al 29 Blood Group-O, individuals were less likely to contract the virus, whereas blood Group-A was associated with an increased risk.…”
Section: Abo Has Four Fundamental Phenotypes: O a Bcontrasting
confidence: 91%
“…In his detailed analysis, Bhattacharjee further supported this with data indicating a higher frequency of Blood Group-A in patients with severe COVID-19. 24 Our study diverges from the results obtained by Rehman FU et al, 25 Hafiz W et al 26 and Bryce E Pasko et al 27 who found no significant association between blood groups and disease severity. In studies by Barnkob et al 28 and Dite et al 29 Blood Group-O, individuals were less likely to contract the virus, whereas blood Group-A was associated with an increased risk.…”
Section: Abo Has Four Fundamental Phenotypes: O a Bcontrasting
confidence: 91%
“…Fazal et al also added to the literature and showed that the B blood group was the most frequent among covid-19 patients in Karachi, followed by O, A and AB. However, according to this study blood groups have no role in predicting the severity of the disease [64].…”
Section: Association With Heart Diseasesmentioning
confidence: 62%
“…Regarding ABO blood types, there were contradictory findings amongst different studies. A study from Pakistan reported a lower occurrence of anosmia or ageusia with blood group O (30.0%) compared to blood group B (39.5%) and lower chances of showing severe symptoms of COVID-19 overall [ 11 ]. A study conducted in Spain concluded otherwise; they found that group O had an increased susceptibility to more severe symptoms [ 5 ].…”
Section: Discussionmentioning
confidence: 99%